A systematic review and meta-analysis of the evidence on inflammation in depressive illness and symptoms in chronic and end-stage kidney disease - Jayakumar, S; Jennings, S; Halvorsrud, K; Clesse, C; Magdi Yaqoob. M; de Carvalho, LA; Bhui, K (Cambridge University Press, 2022)
Background Depression affects approximately 27% of adults with chronic kidney disease (CKD) and end-stage kidney failure (ESKF). Depression in this population is associated with impaired quality of life and increased mortality. The extent of inflammation and the impact on depression in CKD/ESKF is yet to be established. Through a systematic literature review and meta-analysis, we aim to understand the relationship between depression and inflammation in CKD/ESKF patients.